What is behind the ear drum? The microbiology of otitis media and the nasopharyngeal flora in children in the era of pneumococcal vaccination. (1st September 2014) - Mills, Nikki; Best, Emma J; Murdoch, David; Souter, Melanie; Neeff, Michel; Anderson, Trevor; Salkeld, Lesley; Ahmad, Zahoor; Mahadevan, Murali; Barber, Colin; Brown, Colin; Walker, Cameron; et al.
<x xml:space="preserve">Abstract</x> Aim This study aims to describe the microbiology of middle ear fluid (MEF) in a cohort of children vaccinated with Streptococcus pneumoniae conjugate vaccine (PCV7) having ventilation tube insertion. Nasopharyngeal (NP) carriage of otopathogens in these children is compared with children without history of otitis media. Methods Between May and November 2011, MEF and NP samples from 325 children aged <3 years were collected in three major centres in New Zealand at the time of ventilation tube insertion. An age‐matched non‐otitis‐prone comparison group of 137 children had NP samples taken. A questionnaire was completed by both groups. Results Immunisation coverage with at least one dose of PCV7 was 97%. Haemophilus influenzae was cultured in 19.4% of MEF and was polymerase chain reaction (PCR) positive in 43.4%. S. pneumoniae and Moraxella catarrhalis were cultured in <10% of MEF samples but were PCR positive for 23.1% and 38.7%, respectively. H. influenzae was the most common organism isolated from NP samples (60%) in the grommet group, while M. catarrhalis (56%) was the most common in the non‐otitis prone group. S. pneumoniae was more commonly found in the nasopharynx of children with ear disease (41% vs. 29%). 19F was the most prominent S. pneumoniae serotype in NP samples of both groups, but no serotype dominated in MEF. Ninety‐five per cent of H. influenzae isolates were confirmed to be non‐typeable H. influenzae. Conclusion In this cohort of children with established ear disease requiring surgical intervention, non‐typeable H. influenzae is the dominant pathogen in both the nasopharynx and MEF.